Clustering Prevalensi Stunting Balita Menggunakan Agglomerative Hierarchical Clustering - Maulina Rizky Anggraeni; Uky Yudatama; Maimunah Maimunah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Indonesia is a country that still has a high stunting prevalence rate of around 36%, ranking 5th with the highest stunting prevalence rate. According to the WHO (World Health Organization) this figure has not reached the expected rate, which is below 20%. Out of 180 countries in the world, nutrition problems in Indonesia are ranked 117th which is still far behind neighboring countries, such as Malaysia which is ranked 44th, Vietnam is ranked 58th, Thiland is ranked 64th, and Singapore is ranked 12th. have a stunting prevalence rate above 20%. Clustering is the process of analyzing data to group similar data into one class and different from other classes. This research was conducted using the Agglomerative Hierarchical Clustering Average Linkage method with a bottom-up approach. The data used is the prevalence of stunting in Tegalrejo using data totaling 2397 in January for toddlers and 3256 in February. The results of the clustering form 3 levels of stunting prevalence each month which can be translated into low prevalence, moderate prevalence, high prevalence, these labels are obtained based on the mean value in each cluster. From the clustering results, there were 5 villages with a low prevalence of stunting in January and February. In villages with a moderate prevalence of stunting, there were 12 villages in January and 10 villages in February. In villages with a high prevalence of stunting in January there were 4 villages and in February 6 villages. This means that there are additional villages with a high prevalence of stunting.